Desempenho macroeconômico, políticas públicas e taxa de pobreza estadual no Brasil: 1981-2006 - Julio Cesar dos Reis (2008)
Poverty has been an issue in the economic theory for a long time. Even though, there are few researches, even Brazilian, about the relation between poverty and macroeconomic performance, despite of the obviousness of that relation. Moreover, it is observed that, formulation as well as implementation of macroeconomic policies, mainly in underdeveloped countries, have the low inflation and primary surpluses as the goals of the policies rather than the poverty, understanding the latter as a secondary consequence of the success of a well planned macroeconomic policy. The present work pretends to fill this space in the policy debate, through the study of the relation between macroeconomic performance and poverty rate, assuming the fight against poverty as a governmental goal. To study this issue, a panel data structure shall be used with state level data from Brazil between 1981 and 2006. The activity rate as well as unemployment rate will be used as indicators of macroeconomic performance and monetary as well as fiscal policies are the macroeconomic policies studied.